The assessment of thermal comfort performance in bamboo ecotourism infrastructure in the tropical climate of Malaysia - Khairul Nizar, Aina Amira; Sanusi, Aliyah Nur Zafirah; Muhammad, Muhammad Azmeer; Ismail, Mohd Noorizhar; Yusof, Zeenat Begam; Azmin, Aida Kesuma (IFERP Explore, 2023)
Ecotourism has become a growing trend, offering a platform for raising awareness of environmental issues in the tourism industry. One of the principles of ecotourism is relying on environmentally friendly infrastructure to prevent environmental degradation. The shift towards ecotourism has highlighted the significance of sustainable practice and infrastructure design in tourism. Bamboo is gradually renowned due to its role in carbon sequestration, bringing hope to the natural environment despite the slow acceptance by society. Assessing the thermal comfort performance takes on added value in the context of encouraging bamboo utilization for sustainable practice. As bamboo gains recognition for its potential in environmental protection, its thermal comfort attributes could encourage its adoption in future infrastructure. Hence, this study examines the thermal comfort performance in bamboo buildings in Malaysia using various design approaches in the same microclimate. Fieldwork was conducted to analyze the indoor and outdoor temperatures in three different chalets in Tadom Hill Resort, Banting, namely Gendui Chalet, Semantan Chalet, and Hakka Village. Generally, findings concluded that the indoor temperatures are higher than the indoor thermal conditions indicated in Malaysia Standard, MS1525:2007. Findings also indicate that the maximum temperature reduction is 2.4°C, 4.1°C, and 4.6°C for Gendui Chalet, Semantan Chalet, and Hakka Village, respectively. Ultimately, this study seeks to emphasize the feasibility of bamboo as a likely option for building construction, developing, and improving the ecotourism destinations in Malaysia.